Provider independent cryptographic tools - Ibrahim, Subariah; Salleh, Mazleena; Abdul Aziz, Shah Rizan (Faculty of Computer Science and Information System, 2003)
This aim of this research is to provide a library of cryptographic tools which can be used for teaching and further research. The library consists of cryptographic algorithms that include symmetric and asymmetric encryptions, key exchange, hashing algorithms and digital signature algorithms. The library is implemented by using Java cryptographic service provider framework that conforms to Java Cryptographic Architecture (JCA) and Java Cryptographic Extension (JCE). The library is developed using Software Development Life Cycle (SDLC), supported by Unified Modeling Language (UML) for the design. The programming language used is Java JDK1.4.1.